2019
DOI: 10.2478/jeb-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness Modeling of Retail on Emotional Fatigue of Consumers

Abstract: Demand for high-quality shopping service has seen continuous growth in the recent years, allowing retail chains to achieve sustainable competitive advantage, increase number of loyal customers. This in-turn results in demand boosting and image of the firm. To analyze and achieve this emotional reactions of customers while shopping becomes important. The paper attempts to evaluate the effect of emotional fatigue on purchase process and uses neuromarketing tool – Galvanic skin reaction analysis to do so. Changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The emotional freedom technique is a healing technique that combines the power of psychological energy with prayer (Bach et al, 2019;Patterson, 2016). The method uses the primary energy system of the body in eliminating physical and emotional problems (anxiety, anger, panic disorder, addiction to cigarettes and drugs, stress, depression, trauma, fear, and phobia) (Andrii et al, 2019;Bougea et al, 2013;Dewi et al, 2020). The emotional Freedom Technique can also help relieve headaches, insomnia, allergies, cancer (Dewi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The emotional freedom technique is a healing technique that combines the power of psychological energy with prayer (Bach et al, 2019;Patterson, 2016). The method uses the primary energy system of the body in eliminating physical and emotional problems (anxiety, anger, panic disorder, addiction to cigarettes and drugs, stress, depression, trauma, fear, and phobia) (Andrii et al, 2019;Bougea et al, 2013;Dewi et al, 2020). The emotional Freedom Technique can also help relieve headaches, insomnia, allergies, cancer (Dewi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…GSR and ECG were used to measure consumers' emotional valence and arousal to stimuli. For example, store atmosphere, consumer's status, and waiting in the cashier lines influence the emotional fatigue [80], ads with sad messages were more effective [77], each ad generates a different emotional status [20]. IAT to measure the consumers' attitudes (e.g., like, dislike).…”
Section: Discussionmentioning
confidence: 99%
“…Both can measure the autonomic nervous system and evaluate the internal emotional status of consumers [20]. For example, Andrii, et al [80] found that the atmosphere in the store and the consumers' state influence emotional fatigue. Similarly, Halkin [81] found that waiting in the cashier line indicates an increase in the consumer's fatigue index in the shops and decreases on the road back to home.…”
Section: Neuromarketing Tools Used In Studying Consumers' Behavior To...mentioning
confidence: 99%
“…Limit of the Study Andrii, et al (Andrii et al, 2019) Attractiveness modeling of retail on emotional fatigue of consumers…”
Section: Finding Summarymentioning
confidence: 99%